The study of a better complex configuration is included at the highest polar determination of D-lemons with the β-Cyclodextrin by atomic computation - ALI, NORHAN; HOSOUNA, BOUBAKER Muftah (Journal of natural sciences, life and applied sciences, 2019)
The study involved the integration of natural lemons with β-cyclodecxtrin at a different energy levels and angles. A total of 176 computer samples were created using the Gaussian 03 and Hyperchem 08 programs for drawing, integrating, simulating and calculating the dipole moment values, already detect the best and most powerful dipole moment were found at the first level, the internal angle 315o and dipole moment 15.2863 deby, Through these results we obtained the best inclusion complex between lemons and β-cyclodecxtrin,which can be obtained from the industrial application of drugs.
Keywords: d-lemon; beta-cyclodextrin; polar moment